Exposure‒response relationships for silicosis and its progression in industrial sand workers - Pamela M Vacek; Robert E Glenn; Roy J Rando; John E Parker; Jeffrey P Kanne; Daniel A Henry; Cristopher A Meyer (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: This study aimed to characterize the relationship between radiographic silicosis and exposure to respirable quartz and determine how exposure affects disease progression. METHODS: Surveillance chest radiographs from a cohort of 1902 workers were examined to identify 67 cases of radiographic silicosis and 167 matched controls. Exposures were estimated by linking work histories to a job exposure matrix (JEM) based on samples collected by the participating companies and historical estimates. Conditional logistic regression was used to examine exposure‒response relationships. Sequential radiographs from silicosis cases were used to assess associations between exposure and disease progression. RESULTS: Risk of silicosis increased with cumulative exposure [odds ratio (OR) 1.43 per 1 mg/m^3 years, 95% confidence interval (CI) 1.23-1.66], average exposure concentration (OR 1.30 per 0.10 mg/m^3, 95% CI 1.11-1.51) and net exposure duration (OR 1.10 per year, 95% CI 1.05-1.16). Multivariate analyses indicated that the risk associated with cumulative exposure varied depending on exposure duration and concentration. Analysis of the time worked at differing exposure levels indicated that exposures ≤0.05 mg/m^3 were not significantly associated with silicosis risk after adjustment for years worked at higher concentrations. Disease progression was related to subsequent exposure concentration, with a yearly increase in small opacity profusion of 0.052 subcategory per each 0.10 mg/m^3 increase in concentration. CONCLUSIONS: Workers with longer exposure at lower concentrations were at higher risk for silicosis than those with the same cumulative exposure who worked for a shorter time at higher concentrations. The rate of silicosis progression was related to subsequent exposure concentration.